“Propuesta de un texto guía para la enseñanza aprendizaje en la asignatura de contabilidad para los estudiantes de bachillerato en la especialización de contabilidad y administración en el Instituto Superior la Maná”. - Moreira Quiroz, Wilson Manuel (2017)
The objective that generated the present investigation was to design a Text with the programmatic contents of the accounting subject that requires the formation of the bachelor when taking into account the new performance functions since the professional scenarios have also been changing. Currently, training in the specialty of accounting is convenient, to carry out administrative management of treasury and accounting records in a certain institution, the contribution of the guide text becomes support in the teaching-learning process of accounting to raise the level of student performance. . In the process, research methods were used such as: the analysis in the presentation of survey results, the interpretative synthesis in the statistical results, the presentation of the effects of the investigation and scientifically applied in the preparation of the final report. Accounting students should aim to have a profile of specialized technicians in banking accounting from the Higher Institute "La Maná", taking into account that the knowledge acquired with research must be applied.